Transformasi Pembelajaran Sains: Peran Quizizz dalam Meningkatkan Pemahaman Siswa tentang Sumber Energi - Hany Handayani; Mugi Cahya Ramadhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using interactive learning media Quizizz on students' conceptual understanding ability in energy source material. The research method used is Nonequivalent Control Group Design with two groups of students as research samples. The experimental group used Quizizz learning media, while the control group used conventional learning video media. Data were collected through pretest and posttest tests to measure conceptual understanding ability and student response questionnaires used to determine student motivation and response to the learning media used. The results showed a significant increase in the conceptual understanding ability of students who learned using Quizizz media compared to students who learned using video media. Quizizz features such as giving points, leaderboards, and setting work time have proven to be effective in providing additional motivation for students to compete healthily and be more active in learning. The use of Quizizz also makes it easier for teachers to monitor student learning progress in real-time and provide feedback quickly. The positive response from students to this media shows that digital learning technology innovation can be a solution to the problem of low motivation to learn on difficult and abstract subject matter. This study strengthens the argument that interactive learning media is not just a tool, but an important component in designing effective and enjoyable learning strategies for students. The contribution of this study is very important for the development of learning practices, especially for teachers and education practitioners to optimize the use of technology as a learning medium. The implications of the research results show that the integration of innovative digital learning media such as Quizizz can improve the quality of the learning process and student learning outcomes. Therefore, it is recommended that teachers make more use of interactive learning media to support the effectiveness of learning and form competent students in the digital era.